A universal power law for modelling the growth and form of teeth, claws, horns, thorns, beaks, and shells - Evans, Alistair R.; Pollock, Tahlia I.; Cleuren, Silke G. C.; Parker, William M. G.; Richards, Hazel L.; Garland, Kathleen L. S.; Fitzgerald, Erich M. G.; Wilson, Tim E.; Hocking, David P.; Adams, Justin W. (BMC biology, 2021)
A major goal of evolutionary developmental biology is to discover general models and mechanisms that create the phenotypes of organisms. However, universal models of such fundamental growth and form are rare, presumably due to the limited number of physical laws and biological processes that influence growth. One such model is the logarithmic spiral, which has been purported to explain the growth of biological structures such as teeth, claws, horns, and beaks. However, the logarithmic spiral only describes the path of the structure through space, and cannot generate these shapes. Here we show a new universal model based on a power law between the radius of the structure and its length, which generates a shape called a 'power cone'. We describe the underlying 'power cascade' model that explains the extreme diversity of tooth shapes in vertebrates, including humans, mammoths, sabre-toothed cats, tyrannosaurs and giant megalodon sharks. This model can be used to predict the age of mammals with ever-growing teeth, including elephants and rodents. We view this as the third general model of tooth development, along with the patterning cascade model for cusp number and spacing, and the inhibitory cascade model that predicts relative tooth size. Beyond the dentition, this new model also describes the growth of claws, horns, antlers and beaks of vertebrates, as well as the fangs and shells of invertebrates, and thorns and prickles of plants. The power cone is generated when the radial power growth rate is unequal to the length power growth rate. The power cascade model operates independently of the logarithmic spiral and is present throughout diverse biological systems. The power cascade provides a mechanistic basis for the generation of these pointed structures across the tree of life.